2015
DOI: 10.1007/s13204-015-0506-7
|View full text |Cite
|
Sign up to set email alerts
|

First report on rapid screening of nanomaterial-based antimicrobial agents against β-lactamase resistance using pGLO plasmid transformed Escherichia coli HB 101 K-12

Abstract: Combating antibiotic resistance requires discovery of novel antimicrobials effective against resistant bacteria. Herein, we present for the first time, pGLO plasmid transformed Escherichia coli HB 101 K 12 as novel model for screening of nanomaterial-based antimicrobial agents against b-lactamase resistance. E. coli HB 101 was transformed by pGLO plasmid in the presence of calcium chloride (50 mM; pH 6.1) aided by heat shock (0-42-0°C). The transformed bacteria were grown on Luria-Bertani agar containing ampic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…NS is reported to have potent antibacterial effect against many bacterial species [19][20][21]. A previous study reported that NS dressing protects from bacterial contamination in a variety of chronic non-healing wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS is reported to have potent antibacterial effect against many bacterial species [19][20][21]. A previous study reported that NS dressing protects from bacterial contamination in a variety of chronic non-healing wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of nano-particles using various microbes and plant was explored [18][19][20][21]. The biosynthesis of nanoparticles using plant extracts produces green, eco-friendly nanoparticles and also exploits vast plant resources that are widely distributed, easily available, safe to handle and with a range of metabolites [22].…”
Section: Introductionmentioning
confidence: 99%
“…The production of silver, zinc and copper oxide nanoparticles is between 100 and 1000 tons per year globally [7]. Especially, silver nanoparticles (AgNPs) provide enormous hope for use in the medical field by virtue of their broad antimicrobial spectrum against both Gram positive and Gram negative bacteria, including multi‐drug resistant strains [8, 9] and relative non‐toxicity [10]. AgNPs are an attractive choice for therapy in mastitis as bacterial resistance is altogether absent [11, 12].…”
Section: Introductionmentioning
confidence: 99%